PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, AUDIT TENURE, LEVERAGE, DAN KOMITE AUDIT TERHADAP AUDIT DELAY - Yuni Munawaroh (2022)
Audit delay is the time of audit implementation from closing date of the company's book that is December 31 until the audited financial statements are published on the Indonesia Stock Exchange. This study aims to determine the effect of company size, profitability, audit tenure, leverage, and committee audit on audit delay. The study uses companies in the trade, service, and investment sector on the Indonesia Stock Exchange in the 2018-2020 period. Sampling technique using purposive sampling method and obtained 363 data of 121 sample companies during 2018-2020. Testing hypothesis used multiple linier regression analysis with STATA version 14 and a significance level of 5% (0,05). The results of the testing showed that the company size do not have a significant effect on audit delay. Audit tenure, leverage, and committee audit has a positive and significant effect on audit delay, then profitability has a negative and significant effect on audit delay.